2022
DOI: 10.3390/pr10050867
|View full text |Cite
|
Sign up to set email alerts
|

Power Parametric Optimization of an Electro-Hydraulic Integrated Drive System for Power-Carrying Vehicles Based on the Taguchi Method

Abstract: Focused on the troubles and defects introduced by the traditional single form of electric vehicle transmission, this paper proposes an electro-hydraulic power coupled electric vehicle based on the working principle of an electro-hydraulic power integrated drive system for light-duty cargo vehicles. The integration of the planetary row into the drive system allows the interconversion of mechanical, electrical, and hydraulic energy. By describing the system structure and composition, several working conditions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Figure 3 shows the system structure diagram. The new energy storage charging pile system for EV is mainly composed of two parts: a power regulation system [43] and a In this paper, a high-performance energy storage battery is added on the basis of the traditional charging pile. Based on this, a new design scheme of the energy storage charging pile system is proposed [40][41][42].…”
Section: Overall Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows the system structure diagram. The new energy storage charging pile system for EV is mainly composed of two parts: a power regulation system [43] and a In this paper, a high-performance energy storage battery is added on the basis of the traditional charging pile. Based on this, a new design scheme of the energy storage charging pile system is proposed [40][41][42].…”
Section: Overall Designmentioning
confidence: 99%
“…Figure 3 shows the system structure diagram. The new energy storage charging pile system for EV is mainly composed of two parts: a power regulation system [43] and a charge and discharge control system. The power regulation system is the energy transmission link between the power grid, the energy storage battery pack, and the battery pack of the EV.…”
Section: Overall Designmentioning
confidence: 99%
“…The simulation results show that in the Economic Commission for Europe (ECE) and the Extra Urban Driving Cycle (EUDC), the MSEH-HEV has a 15% reduction in battery consumption, and the motor peak torque is significantly reduced. Chen et al 22 proposed a hybrid electric-hydraulic vehicle and several operating conditions during the vehicle's motion. Using the state of charge (SOC) of the battery as a constraint, orthogonal experimental matrices for the electric-hydraulic ratio and speed thresholds under various operating conditions were established based on the Taguchi method.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization results showed that the economy of the electromechanical–hydraulic power coupled electric vehicle is improved under the optimal electric–hydraulic ratio. [ 36 ] Another point worth noting is that the genetic algorithm (GA) is a heuristic algorithm with good optimization performance. [ 37 ] It can easily select a satisfactory solution based on optimization objectives.…”
Section: Introductionmentioning
confidence: 99%